GE_GERICHTE P/1568/2014 vom 19. April 2016 - GE Cour de justice (2016)
MENACE(DROIT PÉNAL); IN DUBIO PRO REO; POUVOIR D'APPRÉCIATION; INTENTION; DOL ÉVENTUEL; DÉPENS; PLAIGNANT | CP.180; CP.12; CPP.433.1.a